Evaluasi Kinerja Pemeliharaan Mesin PLTD dengan Menggunakan Pendekatan Reliability Centered Maintenance (RCM) - Firman, Firman; Linda, Muthia Roza; Suci, Renti Febtri (Jurnal Kajian Manajemen Bisnis, 2017)
Diesel Powered Electric Generator is a Electric Generator where using Diesel Machine as primer mover, which function to produce mechanical energy required to rotate the rotor generator to produce the electricity. The problem faced is found a lot of damage whice is make engine machine does not operate and high repair costs that result the company suffered losses. Reliability Centered Maintenance is a method where used to find â€œwhat should you doâ€ to determine effective treatment. The result Showed that the machine has a major constraint on the machine RUSTON 1 is Injection Pump and Cylinder Linier Infection Pump with maintenance intervals about 44.24 hours. The Failure factor of the engine components are the supply of engineâ€™s fuel is not optimal. Total cost for cumulative maintenance of two critical components reach Rp. 831.263.531. Â Keywords: Maintenance,Â  Reliability Centered Maintenance (RCM)